The Influence of Inlet and Outlet Ratios on the Performance of Natural Ventilation in Mosque, Indonesia - Imron Ahmadi; Agus Hariyadi (Journal of Artificial Intelligence in Architecture, 2025)
Natural Ventilation is a sustainable passive strategy for enhancing thermal comfort and reducing energy consumption in buildings with fluctuating occupancy levels, such as mosques. This study investigates the effects of varying inlet-to-outlet opening ratios using different schemes, simulated through Computational Fluid Dynamics (CFD) with the RANS model via OpenFOAM (Butterfly plugin in Grasshopper). Based on urban wind profiles, this research evaluates wind-driven Ventilation under isothermal conditions. The simulation examines five inlet-outlet opening ratios (ranging from 1:1 to 1:5), two inlet configurations (single vs. double), five building lengths (5×10, 10×10, 15×10, 20×10, and 25×10 m), and three building heights (3 m, 4 m, and 5 m). Results indicate that an opening ratio of 1:3 provides the optimal balance between airflow efficiency and thermal stability, particularly concerning solar radiation effects. The single-inlet configuration yields higher air velocity at standing height (1.1 m), whereas the double-inlet setup promotes a more uniform vertical airflow distribution. Increasing building height enhances airflow due to reduced ground-level resistance, while elongated floor plans (over 10 m in length) experience flow stagnation in the central zone. These findings underscore that optimal natural ventilation in mosques depends on opening ratios, spatial proportions, and inlet configurations. Such insights contribute to climate-responsive mosque design, especially in dense urban environments, supporting energy-efficient and comfortable indoor conditions during congregational prayers.